A rare case of multifocal craniospinal leptomeningeal melanocytoma: A case report and scoping review - Daniel Lewis; Timothy P. Dawson; Rebecca Hyde; George Adrian Rata; Andrew F. Alalade; Kaushik Ghosh; Ahmed Elhabal (Brain and Spine)
Introduction: Leptomeningeal melanocytomas are rare tumours originating from neural crest derived melanocytes. They are usually solitary and presentation with multifocal meningeal melanocytoma is very rare and indicative of potentially more aggressive behaviour. This case report and scoping review sought to evaluate the presentation, and key radiological features that can help differentiate multifocal meningeal melanocytoma from other differentials and provide a discussion of the key management and prognostic points once these tumours are diagnosed. Case presentation: A 26 year old male presented with neck pain radiating to both shoulders and subjective weakness in left shoulder movement. MRI demonstrated a large enhancing C2–C3 intradural-extramedullary lesion with further lesions at the T7/T8 level, left cerebellopontine angle and midline suprachiasmatic region. Whilst the imaging appearances were initially thought be indicative of a phacomatosis such as NF2-related schwannomatosis, surgical excision of the cervical tumour confirmed a melanocytic tumour of leptomeningeal origin, consistent with multifocal meningeal melanocytoma. Patient made a good post-operative recovery and remains under half yearly radiological surveillance, with repeat MRI 6 months after surgery demonstrating subtle growth of the untreated intracranial and spinal lesions. Literature review and conclusions: This is the first description, to our knowledge, of a multifocal meningeal melanocytoma associated with both cerebellopontine angle and suprasellar lesions. This case and included scoping review highlight the need to consider this rare diagnosis whenever multifocal craniospinal lesions are encountered, and the need to consider aggressive management through surgical resection and adjuvant craniospinal radiotherapy once these tumours are diagnosed.